2022
DOI: 10.1103/physrevlett.128.112501
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond-Scale Proton Emission from Strongly Oblate-Deformed Lu149

Abstract: Using the fusion-evaporation reaction 96 Ruð 58 Ni; p4nÞ 149 Lu and the MARA vacuum-mode recoil separator, a new proton-emitting isotope 149 Lu has been identified. The measured decay Q value of 1920( 20) keV is the highest measured for a ground-state proton decay, and it naturally leads to the shortest directly measured half-life of 450 þ170 −100 ns for a ground-state proton emitter. The decay rate is consistent with l p ¼ 5 emission, suggesting a dominant πh 11=2 component for the wave function of the proton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Nine prompt (including two tentative) γ-ray transitions have been observed that are associated with a short-lived β-decaying A = 94 nucleus, produced via the 1p3n charged-particle evaporation channel, and whose half-life is consistent with the currently accepted value for the 94 Ag ground-state β-decay. A new proton-emitting isotope 149 Lu has been identified using the fusion-evaporation reaction 96 Ru( 58 Ni,p4n) 149 Lu and the MARA separator [105]. The measured decay Q value of 1920 (20) keV has been the highest measured for a ground-state proton decay.…”
Section: The Jyväskylä Accelerator Laboratory University Of Jyväskylä...mentioning
confidence: 98%
“…Nine prompt (including two tentative) γ-ray transitions have been observed that are associated with a short-lived β-decaying A = 94 nucleus, produced via the 1p3n charged-particle evaporation channel, and whose half-life is consistent with the currently accepted value for the 94 Ag ground-state β-decay. A new proton-emitting isotope 149 Lu has been identified using the fusion-evaporation reaction 96 Ru( 58 Ni,p4n) 149 Lu and the MARA separator [105]. The measured decay Q value of 1920 (20) keV has been the highest measured for a ground-state proton decay.…”
Section: The Jyväskylä Accelerator Laboratory University Of Jyväskylä...mentioning
confidence: 98%
“…For example, see Ref. [16] for the recently discovered strongly oblate deformed proton emitter 149 Lu. In order to discuss the sign of the quadrupole deformation parameter β 2 , or if one follows the Lund convention, the triaxiality parameter γ , the levelspacing in the (rotational) band feeding the proton-emitting state should be measured.…”
mentioning
confidence: 99%
“…The linear energy response of the DSSD was calibrated using a 151 Lu proton-decay activity (offset parameter) and standard α source (gain parameter) containing 239 Pu, 241 Am, and 244 Cm activities. The 151 Lu decay data were obtained in an experiment performed prior to the present work [16]. The recoils were distinguished from other implantation events based on the MWPC-DSSD time-of-flight information and on Events / (5 keV x 0.1 pixel)…”
mentioning
confidence: 99%